Recurrent NRAS mutations in pulmonary Langerhans cell histiocytosis. Issue 6 (13th April 2016) - Mourah, Samia; How-Kit, Alexandre; Meignin, Véronique; Gossot, Dominique; Lorillon, Gwenaël; Bugnet, Emmanuelle; Mauger, Florence; Lebbe, Celeste; Chevret, Sylvie; Tost, Jörg; Tazi, Abdellatif
The mitogen-activated protein kinase (MAPK) pathway is constantly activated in Langerhans cell histiocytosis (LCH). Mutations of the downstream kinases BRAF and MAP2K1 mediate this activation in a subset of LCH lesions. In this study, we attempted to identify other mutations which may explain the MAPK activation in nonmutated BRAF and MAP2K1 LCH lesions. We analysed 26 pulmonary and 37 nonpulmonary LCH lesions for the presence of BRAF, MAP2K1, NRAS and KRAS mutations. Grossly normal lung tissue from 10 smoker patients was used as control. Patient spontaneous outcomes were concurrently assessed. BRAF V600E mutations were observed in 50% and 38% of the pulmonary and nonpulmonary LCH lesions, respectively. 40% of pulmonary LCH lesions harboured NRAS Q61K / R mutations, whereas no NRAS mutations were identified in nonpulmonary LCH biopsies or in lung tissue control. In seven out of 11 NRAS Q61K / R -mutated pulmonary LCH lesions, BRAF V600 E mutations were also present. Separately genotyping each CD1a-positive area from the same pulmonary LCH lesion demonstrated that these concurrent BRAF and NRAS mutations were carried by different cell clones. NRAS Q61K / R mutations activated both the MAPK and AKT (protein kinase B) pathways. In the univariate analysis, the presence of concurrent BRAF V600E and NRAS Q61K / R mutations was significantly associated with patient outcome. These findings highlight the importance of NRAS genotyping of pulmonary LCH lesions because the use of BRAF inhibitors in this context may lead to paradoxical disease progression. These patients might benefit from MAPK kinase inhibitor-based treatments. Pulmonary Langerhans cell histiocytosis genetic landscape includes recurrent activating NRAS Q61 mutations http://ow.ly/YgsSm